Distinct roles of BCNP1 in B-cell development and activation. (15th August 2019) - Hong, Rongjian; Lai, Nannan; Xiong, Ermeng; Ouchida, Rika; Sun, Jiping; Zhou, Yang; Tang, Yue; Hikida, Masaki; Tsubata, Takeshi; Tagawa, Masatoshi; Wang, Yanqing; Wang, Ji-Yang
Abstract : BCNP1 regulates a wide variety of B cell functions Abstract: B-cell novel protein 1 (BCNP1) has recently been identified as a new B-cell receptor (BCR) signaling molecule but its physiological function remains unknown. Here, we demonstrate that mice deficient in BCNP1 exhibit impaired B-cell maturation and a reduction of B-1a cells. BCNP1-deficient spleen B cells show enhanced survival, proliferation and Ca 2+ influx in response to BCR cross-linking as compared with wild-type spleen B cells. Consistently, mutant B cells show elevated phosphorylation of SYK, B-cell linker protein (BLNK) and PLCγ2 upon BCR cross-linking. In vivo, BCNP1-deficient mice exhibit enhanced humoral immune responses to T-independent and T-dependent antigens. Moreover, aged mutant mice contain elevated levels of serum IgM and IgG3 antibodies and exhibit polyclonal and monoclonal B-cell expansion in lymphoid organs. These results reveal distinct roles for BCNP1 in B-cell development, activation and homeostasis.